Phineas P. Quimby papers - Quimby, P. P. (Phineas Parkhurst), 1802-1866.; Burkmars, Lucius E.
Drafts of letters, handwritten copies of essays, and notes for essays or lectures by Quimby on such subjects as wisdom, happiness, religion, life and death, and mind and matter, as well as accounts of his experiences in healing. Includes letters (1862-1865) from Mary M. Patterson (Mary Baker Eddy) to Quimby and a journal of his associate, Lucius E. Burkmars.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
Healer and spiritualist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Eddy, Mary Baker, -- 1821-1910 -- Correspondence; Mental healing; Religion; Spiritualism; Healers; Spiritualists